2017
DOI: 10.1021/acsami.7b15673
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Efficient Fluorescence Emission from Cucurbit[10]uril-[Cd4Cl16]8–-Based Pillared Diamond Porous Supramolecular Frameworks

Abstract: Cucurbit[10]uril (Q[10] or CB[10]), with the largest rigid cavity (ca. 1.0 nm) yet characterized in the cucurbiturils family, and indeed among all artificial macrocyclic receptors to date, has been successfully exploited to construct a novel Q[10]-[CdCl]-based pillared diamond porous supramolecular framework. Single-crystal X-ray diffraction analysis revealed that the three-dimensional open-nanotube-type porous framework is constructed from free Q[10] molecules and [CdCl] cluster anions through the outer surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…[6]-Based Porous Supramolecular Framework. Quite a few experimental results have proven that Q[n]-based porous supramolecular frameworks can take up various dyes and fused ring compounds and form solid fluorescent assemblies [29,30]. In the present case, different pores, gaps, spaces, and channels can be observed in the TMeQ immersing A in an acetonitrile solution containing FG6 yielded luminescent material FG6@A that exhibited a ∼2.5fold increase in fluorescence enhancement compared with the free FG6 (Figure 3(a)).…”
Section: Crystal Structures Of Compounds a Various Tmeq[6]-mentioning
confidence: 59%
See 3 more Smart Citations
“…[6]-Based Porous Supramolecular Framework. Quite a few experimental results have proven that Q[n]-based porous supramolecular frameworks can take up various dyes and fused ring compounds and form solid fluorescent assemblies [29,30]. In the present case, different pores, gaps, spaces, and channels can be observed in the TMeQ immersing A in an acetonitrile solution containing FG6 yielded luminescent material FG6@A that exhibited a ∼2.5fold increase in fluorescence enhancement compared with the free FG6 (Figure 3(a)).…”
Section: Crystal Structures Of Compounds a Various Tmeq[6]-mentioning
confidence: 59%
“…In general, loading porous framework A with a fluorescent guest could change conformation or aggregation state of the fluorescent guest and result in its fluorescence enhancement or quenching. Recent studies have shown that Q[n]-based supramolecular assemblies or frameworks can adsorb a variety of VOCs, whereas the adsorbed VOC could influence the florescence properties of the resulting FG@A luminescent materials [29,30]. us, the adsorption of 12 common VOCs was tested: dichloromethane, trichloromethane, tetrachloromethane, methanol, ethanol, acetone, acetonitrile, ethyl ether, benzene, toluene, formaldehyde, and tetrahydrofuran.…”
Section: Crystal Structures Of Compounds a Various Tmeq[6]-mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, RhB@MOF could also be used to differentiate molecules with very similar structures such as o -, m - and p -xylenes, as well as fluoro-, chloro-, and bromobenzenes, rendering it a useful luminescent probe for the sensing of VOCs. A supramolecular cadmium framework was also prepared using cucurbit[10]uril (CB[10]) as the organic linker (Yao et al, 2017 ). Upon the encapsulation of rhodamine B, pyrenemethanamine hydrochloride and bathocuproine hydrochloride, the framework was observed to exhibit red-green-blue fluorescence, respectively.…”
Section: Mof-based Composite Materials For Dye Adsorptionmentioning
confidence: 99%